2021
DOI: 10.1097/md.0000000000026240
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of sit training for patients with severe COVID-19 pneumonia during deep sedation

Abstract: Rationale: There have been a few reports on the early rehabilitation of patients with coronavirus disease (COVID-19), and none on the effectiveness and adverse events of early mobilization for mechanical ventilation patients (other than COVID-19) during deep sedation. This report indicates that sitting without adverse events is possible in patients with severe COVID-19 pneumonia during deep sedation with muscle relaxation. Patient concerns: A 65-year-old man with a hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…Several studies have reported rehabilitation for patients with COVID-19 pneumonia (14)(15)(16)(17)(18). However, to the best of our knowledge, there have been no reports of rehabilitation for patients with MIS-C.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have reported rehabilitation for patients with COVID-19 pneumonia (14)(15)(16)(17)(18). However, to the best of our knowledge, there have been no reports of rehabilitation for patients with MIS-C.…”
Section: Discussionmentioning
confidence: 98%
“…Excessive fluid replacement to correct the decrease in circulating plasma volume can cause pulmonary edema. However, previous studies have noted that early gravity loading in a sitting or standing position, with an abdominal bandage and elastic stockings as an active rehabilitation intervention, may increase the circulating plasma volume and prevent the occurrence of symptomatic pulmonary edema 31,32 . In addition, physical therapy interventions such as positional drainage for atelectasis can prevent symptomatic respiratory failure or pneumonia by improving the patient’s airway clearance 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Early mobilization of ICU patients effectively reduces the time to extubation and duration of hospital stay and improves the ADL [7]. Additionally, early rehabilitation has been recently recommended for patients with COVID-19 in the ICU [5,8,9]. Despite numerous concerns regarding the rehabilitation of patients with severe COVID-19 pneumonia, a consensus has been reached on several fronts, including respiratory training, moderate head elevation, limb mobilization, and sitting and standing positions at the bedside [18].…”
Section: Discussionmentioning
confidence: 99%
“…Early mobilization of ICU patients effectively reduces the duration of intubation and hospital stay and improves ADL [7]. In our hospital, the Department of Emergency and Critical Care Medicine and the Department of Rehabilitation collaborated to implement early mobilization from the early phase of ICU admission, with the same protocol being applied to patients with severe COVID-19 pneumonia [8,9]. However, since COVID-19 is a new disease, there remains scarce information regarding rehabilitation.…”
Section: Introductionmentioning
confidence: 99%